Histological evaluation of capsules formed by silicon implants coated with polyurethane foam and with a textured surface in rats - Silva,Eduardo Nascimento (2016)
ABSTRACT PURPOSE: To assess the capsules formed by silicone implants coated with polyurethane foam and with a textured surface. METHODS: Sixty-four Wistar albinus rats were divided into two groups of 32 each using polyurethane foam and textured surface. The capsules around the implants were analyzed for 30, 50, 70 and 90 days. Were analyzed the following parameters: foreign body reaction, granulation tissue, presence of myofibroblasts, neoangiogenesis, presence of synovial metaplasia, capsular thickness, total area and collagen percentage of type I and III, in capsules formed around silicone implants in both groups. RESULTS: The foreign body reaction was only present in the four polyurethane subgroups. The formation of granulation tissue and the presence of myofibroblasts were higher in the four polyurethane subgroups. Regarding to neoangiogenesis and synovial metaplasia, there was no statistical difference between the groups. Polyurethane group presented (all subgroups) a greater capsule thickness, a smaller total area and collagen percentage of type I and a higher percentage area of type III, with statistical difference. CONCLUSION: The use of polyurethane-coated implants should be stimulated by the long-term results in a more stable capsule and a lower incidence of capsular contracture, despite developing a more intense and delayed inflammatory reaction in relation to implants with textured surface.